1974
DOI: 10.1136/jnnp.37.10.1093
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial volume-pressure relationships during experimental brain compression in primates: 1. Pressure responses to changes in ventricular volume

Abstract: SYNOPSIS Intermittent additions of 0 05 ml saline were made into the lateral ventricle of anaesthetized, ventilated baboons at regular intervals during continuous inflation of a supratentorial extradural balloon. Close correlation was observed both between the increase in ventricular fluid pressure (VFP) immediately after the injection and the volume in the balloon (P < 0001); and between the increase in ventricular pressure and the pressure immediately before the injection (P < 0001). This change in ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Although several studies have examined the and experimental studies have shown a direct relationship between VFP and VPR (Leech and Miller, 1974a). If the volumepressure curve remains unaltered, therefore, a reduction in VFP produced by mannitol should be accompanied by an equal reduction in VPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have examined the and experimental studies have shown a direct relationship between VFP and VPR (Leech and Miller, 1974a). If the volumepressure curve remains unaltered, therefore, a reduction in VFP produced by mannitol should be accompanied by an equal reduction in VPR.…”
Section: Discussionmentioning
confidence: 99%
“…During continuous brain compression in baboons this measurement, termed the volume-pressure response (VPR), was found to correlate closely with VFP (before induced ventricular volume change) and with balloon volume (Leech and Miller, 1974a). Measurement of the VPR also provides useful information in patients during continuous monitoring of intracranial pressure .…”
mentioning
confidence: 95%
“…The experimental model is similar to that used in earlier experiments and the anaesthetic, surgical preparation and method of continuously recording systemic arterial pressure (SAP) and VFP have been previously described (Leech and Miller, 1974a). Normocapnia (PCO2 37-44 mmHg) was maintained throughout each experiment.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This response is related to the VFP (Miller et al, 1973a) and even more closely to the degree of intracranial shift seen radiologically in patients with head injuries (Miller and Pickard, 1974). In a previous experimental study (Leech and Miller, 1974a), VPR correlated closely with the volume of an expanding intracranial balloon, and with the VFP.…”
mentioning
confidence: 93%
“…Marmarou et al [3], Sklar and Elashvili [4], Rekate et al [5] and others [6][7][8] have shown that the relationship between ICP and volume is exponential, and Sivaloganathan et al [9] have demonstrated that all of the pressure-volume models can be derived as special cases of a general differential equation that relates CSF pressure to compliance, fluid resistance and CSF formation and absorption:…”
Section: Introductionmentioning
confidence: 99%